Respuesta :

Answer:

Step-by-step explanation:

Its the third choice    c = (ab - d) / a

Divide both sides by a:-

b - c = d/a

b - d/a = c

c =  (ab - d ) / a

Answer:

[tex]c=\frac{ab - d }{a}[/tex]

Step-by-step explanation:

Given equation,

a ( b - c ) = d ----(1)

For finding the formula for c by this equation,

We need to isolate c in the left side of the equation,

By applying distributive property in equation (1),

ab - ac = d

Subtracting ab on both sides,

-ac = d - ab

Divide both sides by -a

[tex]c=\frac{ab - d }{a}[/tex]

Which is the equation for c.

THIRD option is correct.

ACCESS MORE